Topographic data generated from Radarsat Images Over West Kalimantan, Indonesia - Ismullah, Ishak Hanafiah; Nurtyawan, Rian (Journal of Engineering and Technological Sciences, 2005)
Â Indonesia is a tropical country which has dominant cloud coverage, and some of the area has cloud cover almost all year long. Mapping by optical sensors, especially with Photogrammetric method shows a very good result, but the main constraint is cloud cover conditions, and this was the weakness point of this method.This study describe the technique for deriving Topographic data from Radarsat Synthetic Aperture Radar stereo image pair and apply it to an image pair over West Kalimantan, Indonesia. This paper contains also brief discussion of the use of stereo SAR to derive Digital Elevation Model, the site condition and the source of validation data. The result shows that Radarsat data recommended only for 1 : 100.000 or smaller.